Optimalisasi Peran Filantropi Islam ( Zakat Dan Wakaf ) Dalam Pembangunan Pendidikan Yang Berkelanjutan Pada Madrasah Adiniya Al - Munawarah Kecamatan Payaraman - Nur Farhanah; Zuul Fitriani Umari (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the optimization of Islamic philanthropy in the form of zakat and waqf in supporting sustainable educational development at Madrasah Diniyah Al-Munawarah, Payaraman District. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings show that the collection of zakat and waqf is still simple and depends on voluntary community participation without a structured system. In terms of distribution, zakat is mainly used to support teachers’ welfare, while waqf is utilized for the development of educational facilities. The use of zakat funds tends to be consumptive, whereas waqf is more productive as it supports long-term educational infrastructure. The management of zakat and waqf is not yet professional due to limited human resources and the absence of an organized administrative system. The effectiveness of fund utilization shows that zakat and waqf provide real benefits for teachers, students, and the community, although still limited. However, several obstacles exist, such as unstable economic conditions of the community, unstructured management, and suboptimal utilization. Thus, it can be concluded that zakat and waqf have contributed to the sustainability of education at Madrasah Diniyah Al-Munawarah, but their implementation is not yet optimal. Therefore, more professional and structured management is needed to support sustainable education.